AI-ASSISTED EDITING AND OPTIMIZATION OF SCIENTIFIC TEXTS: OPPORTUNITIES AND CHALLENGES (International journal of artificial intelligence, 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed the field of academic writing by providing tools for editing, refining, and optimizing scientific texts. This study explores the opportunities and challenges associated with AI-assisted scientific text editing, focusing on improvements in linguistic accuracy, structural coherence, and stylistic consistency. AI tools contribute to plagiarism detection, terminology standardization, and enhanced logical flow, thereby supporting both native and non-native English-speaking researchers. The analysis emphasizes that AI functions as a supportive instrument, while authors retain responsibility for intellectual content, originality, and contextual interpretation. Ethical considerations, including the risk of over-reliance on automation and potential homogenization of writing styles, are discussed. The study concludes that responsible and informed integration of AI can enhance the quality, efficiency, and accessibility of scientific publications while maintaining academic integrity.